Identification of a mutation at codon 65 in the IKKK motif of reverse transcriptase that encodes human immunodeficiency virus resistance to 2',3'-dideoxycytidine and 2',3'-dideoxy-3'-thiacytidine. - Gu, Z (1994)
The technique of in vitro selection was used to generate variants of the human immunodeficiency virus type 1 that are resistant to 2',3'-dideoxycytidine (ddC). Most of the pol regions of such viruses, including the complete reverse transcriptase open reading frame and portions of flanking protease and integrase genes, were cloned and sequenced, using PCR-based procedures. Mutations were variously detected at amino acid site 65 (Lys-->Arg; AAA-->AGA) and at a previously reported codon, site 184 (Met-->Val; ATG-->GTG). We introduced the site 65 mutation into the pol gene of infectious, cloned HxB2-D DNA by site-directed mutagenesis in order to confirm by viral replication assay the importance of this site in conferring resistance to ddC. The recombinant virus possessed greater than 10-fold resistance against this compound in comparison with parental HxB2-D. Cross-resistance of approximately 20- and 3-fold, respectively, was detectable against the (-) enantiomer of 2',3'-dideoxy-3'-thiacytidine and 2',3'-dideoxyinosine but not against 3'-azido-3'-deoxythymidine. Combinations of the site 65 and 184 mutations did not yield levels of resistance higher than those attained with the site 65 mutation alone. The presence of the site 65 mutation was confirmed by PCR analysis of peripheral blood mononuclear cells from patients on long-term ddC therapy in 4 of 11 cases tested. Viruses that possessed a ddC resistance phenotype were isolated from subjects whose viruses contained the site 65 mutation in each of four instances. Four of these clinical samples were also demonstrated to possess the Met-184-->Val mutation, and one of them possessed both the Lys-65-->Arg and Met-184-->Val substitutions. Direct cloning and sequencing revealed the site 65 mutation in viruses isolated from these individuals.